Tensions and contradictions in government interventions for the promotion of breastfeeding - Rosa María Ramos Rodríguez; María Gabriela Hernández González (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
With the purpose of shedding light on the decrease in the practice of breastfeeding in rural areas of Mexico, this article looks at the current biomedical model and the policies and actions to promote breastfeeding derived from the model's theoretical approach. The article also discusses operational strategies of the governmental social welfare program Oportunidades. For this purpose, the study utilizes the testimonies of 39 young breastfeeding mothers, 11 mothers and grandmothers and 12 members of the health staff in the Nahuatl population of Cuentepec, Morelos, Mexico, which were collected during a previous study in 2008 and 2009. It was found that the biomedical model, which permeates all actions to promote breastfeeding, reifies people, limits communication, devaluates women's traditional knowledge and imposes a discourse that gradually discourages the practice of breastfeeding. The article's proposal is to adopt an epistemic change in biomedical thought that shifts from a paradigm of simplicity to one of complexity, with the purpose of achieving a greater understanding of the bio-psycho-socio-cultural processes of human beings.